Implementation of Transtheoretical Model Nutrition Education and Chromium Picolinate Supplementation on Improved Dietary Adherence Behavior, Chromium Consumption Pattern and Blood Glucose Level Diabetes Mellitus Patients - Lely Cintari; Desak Putu Sukraniti (JURNAL NUTRISIA, 2022)
Bali is one of the provinces in Indonesia that has a Diabetes Mellitus rate above the national prevalence. According to the results of the 2020 study, 56.9% of DM patients did not understand diet education and did not comply with the diet by 56.9% with abnormal blood glucose levels of 63.9%. The results confirmed that repeated exposure with the right method, especially with The theoretical model is very effective in increasing knowledge and adherence to diet and chromium consumption patterns in DM patients. Chromium is effective in improving blood glucose levels in people with Diabetes Mellitus (Types 1 and 2). Chromium improves glucose metabolism in patients with prediabetic glucose intolerance and all women with gestational diabetes. The purpose of this study was to determine the role of nutrition education using a transtheoretical model and the effect of chromium picolinate supplementation on dietary adherence behavior, chromium consumption patterns, and blood glucose levels in patients with diabetes mellitus. This type of research is quasi-experimental. The research design used was one group pretest-posttest. This design does not use a comparison group (control) but uses the first observation (pretest) which allows testing the changes that occur after the experiment or program (Notoatmodjo, 2010). The study was conducted at the Denpasar Health Center. The results showed that there were differences in the level of knowledge and consumption of chromium and blood glucose levels in DM patients. However, there was no difference in the attitude and level of dietary compliance of DM patients.